Wide-band, low-frequency pulse profiles of 100 radio pulsars with LOFAR - Pilia, M.; Hessels, J.; Stappers, B.; Kondratiev, V.; Kramer, M.; van Leeuwen, J.; Weltevrede, P.; Lyne, A.; Zagkouris, K.; Hassall, T.; Bilous, A.; Breton, R.; et al. (2016)
© ESO, 2016. Context. LOFAR offers the unique capability of observing pulsars across the 10-240 MHz frequency range with a fractional bandwidth of roughly 50%. This spectral range is well suited for studying the frequency evolution of pulse profile morphology caused by both intrinsic and extrinsic effects such as changing emission altitude in the pulsar magnetosphere or scatter broadening by the interstellar medium, respectively. Aims. The magnitude of most of these effects increases rapidly towards low frequencies. LOFAR can thus address a number of open questions about the nature of radio pulsar emission and its propagation through the interstellar medium. Methods. We present the average pulse profiles of 100 pulsars observed in the two LOFAR frequency bands: high band (120-167 MHz, 100 profiles) and low band (15-62 MHz, 26 profiles). We compare them with Westerbork Synthesis Radio Telescope (WSRT) and Lovell Telescope observations at higher frequencies (350 and 1400 MHz) to study the profile evolution. The profiles were aligned in absolute phase by folding with a new set of timing solutions from the Lovell Telescope, which we present along with precise dispersion measures obtained with LOFAR. Results. We find that the profile evolution with decreasing radio frequency does not follow a specific trend; depending on the geometry of the pulsar, new components can enter into or be hidden from view. Nonetheless, in general our observations confirm the widening of pulsar profiles at low frequencies, as expected from radius-to-frequency mapping or birefringence theories.